Memorandum of Agreement MoA Work Based Learning WBL between Pusat Sains Matematik UMP and Involve Asia Technologies Sdn Bhd - Noratikah, Abu (Pusat Sains Matematik UMPSA, 2023)
A discussion on the “Memorandum of Agreement (MoA) for Work Based Learning (WBL) Education” between the Center for Mathematical Sciences (PSM), Universiti Malaysia Pahang (UMP) and Involve Asia Technologies Sdn Bhd for the Bachelor of Applied Science in Data Analytics with Honours (2u2i Mode) has taken place virtually on 24 May 2023.